An energy-efficient multi-channel MAC protocol for linear sensor network - Fei TONG; Rucong SUI; Yu CHEN; Heng SU; Hengrui LIU; Shangfeng SU; Yuke YAN (物联网学报)
Sensor nodes in linear sensor network (LSN) are deployed linearly due to the linear topology of the monitoring area.Most of the state-of-the-art medium access control (MAC) protocols designed for LSN adopted the duty-cycling and pipelined-forwarding (DCPF) schemes.They can reduce data propagation delay and network energy consumption but may still cause issues such as transmission competition, interference, and energy hole.To address these issues, an improved DCPF MAC protocol was proposed based on multiple channels and redundant-node deployment for LSN.The extensive simulations based on OPNET demonstrate that, compared with existing protocols, the proposed protocol shows a better performance in terms of energy efficiency, packet delivery ratio, throughput, and packet transmission latency.